2005
DOI: 10.2337/diabetes.54.4.1185
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of HNF4A Polymorphisms in Caucasian-American Type 2 Diabetes

Abstract: Hepatocyte nuclear factor 4␣ (HNF4A), the gene for the maturity-onset diabetes of the young type 1 monogenic form of type 2 diabetes, is within the type 2 diabeteslinked region on chromosome 20q12-q13.1 and, consequently, is a positional candidate gene for type 2 diabetes in the general population. Previous studies have identified only a few rare coding mutations. However, recent studies suggest that single nucleotide polymorphisms (SNPs) located near the P2 (␤-cell) promoter of HNF4A are associated with diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 32 publications
(40 reference statements)
3
36
0
Order By: Relevance
“…However, our result was consistent with that reported in two recent articles published by Bagwell et al (20) and Winckler et al (21), who reported no evidence of any association of single SNPs with type 2 diabetes in Scandinavians and American Caucasians. These discrepant results among the studies may be attributable to the different genetic backgrounds of the subjects.…”
Section: ϫ4supporting
confidence: 82%
See 1 more Smart Citation
“…However, our result was consistent with that reported in two recent articles published by Bagwell et al (20) and Winckler et al (21), who reported no evidence of any association of single SNPs with type 2 diabetes in Scandinavians and American Caucasians. These discrepant results among the studies may be attributable to the different genetic backgrounds of the subjects.…”
Section: ϫ4supporting
confidence: 82%
“…Ϫ27 kb upstream of the P2 promoter, and rs6073418, 17kb downstream of the P2 promoter, represents one block of strong LD, which is consistent with previous reports (15,16,20). No difference in the distributions of either the genotypes or the SNPs in HNF4A were observed between the nondiabetic and type 2 diabetic subjects (Table 1).…”
Section: The Hnf-4␣ Gene and Type 2 Diabetessupporting
confidence: 81%
“…This observation is consistent with observations in many populations emphasizing the role of variants in HNF4A in the manifestation of T2D (Figure 1). 5,6,[19][20][21][22][23][24][25][26][27][28][29] Meta-analysis revealed that the trend for the elevated OR, as found here in North Indians, is seen in 10 other populations. Notably, rs1884613 has higher effect size in North Indians (OR¼1.35 (95%CI 1.17-1.54)) compared with pooled Scandinavian subjects (OR¼1.14 (95%CI 1.06-1.23)), lesser only to Ashkenazi population (OR¼1.70 (95%CI 1.23-2.38)).…”
Section: Discussionmentioning
confidence: 70%
“…The haplotype bearing all "protective" alleles (Hap 3 in Table 3) was present at a frequency of 7.8% and was not associated. Two previous studies (7,10) have identified rare haplotypes within the disequilibrium block encompassing the P2 promoter region, which are significantly associated with type 2 diabetes, although the individual SNPs themselves were not associated. In each study, the associated haplotypes involve rare recombination events between SNP rs2144908 and either rs1884614 or rs1884613.…”
Section: Resultsmentioning
confidence: 99%